Problematika Pemahaman Teks Narasi Pada Siswa Kelas VI SDN Pleret Lor - Firmansyah Miftafurohim; Rochmiyati, Siti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Comprehending narrative literature is a pressing matter for students. Reading entails more than the visual perception of symbols; it involves comprehending the significance conveyed by those symbols. This research aims to identify issues or difficulties in comprehending narrative texts during reading. The objective of this study is to delineate the difficulties encountered by grade VI students at SDN Pleret Lor in comprehending narrative reading texts. This study employs a descriptive methodology. The researchers selected a sample of 40 children in the sixth grade, with 3 of them being chosen as participants. The researchers employed observation and experimentation methodologies. The observation approach is employed to assess students' comprehension by gauging their grasp of the content conveyed through narrative in reading materials. The exam administered to the three kids had the lowest level of reading comprehension. The findings revealed that students encountered difficulties in comprehending narrative texts. Specifically, students struggled with understanding reading comprehension indicators, identifying the main idea of the text, comprehending the information presented, determining factual details, and drawing conclusions from the reading material. Recommendations for educators to employ more effective reading techniques and educators to evaluate reading comprehension.